2011
DOI: 10.1186/1752-1947-5-496
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of a sellar hemangioblastoma due to pituitary apoplexy: a case report

Abstract: IntroductionHemangioblastomas are rare, benign tumors occurring in any part of the nervous system. Most are found as sporadic tumors in the cerebellum or spinal cord. However, these neoplasms are also associated with von Hippel-Lindau disease. We report a rare case of a sporadic sellar hemangioblastoma that became symptomatic due to pituitary apoplexy.Case presentationAn 80-year-old, otherwise healthy Caucasian woman presented to our facility with severe headache attacks, hypocortisolism and blurred vision. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Although all of our hemorrhagic presentations occurred in posterior fossa tumors, several case reports exist of supratentorial (8,28) or intraspinal hemorrhagic hemangioblastomas (8,14,19,26), thus mandating inclusion of hemorrhagic hemangioblastoma on the differential diagnosis of any hemorrhagic lesion.…”
Section: Discussionmentioning
confidence: 95%
“…Although all of our hemorrhagic presentations occurred in posterior fossa tumors, several case reports exist of supratentorial (8,28) or intraspinal hemorrhagic hemangioblastomas (8,14,19,26), thus mandating inclusion of hemorrhagic hemangioblastoma on the differential diagnosis of any hemorrhagic lesion.…”
Section: Discussionmentioning
confidence: 95%
“…[ 16 ] On reviewing the literature from 1902 to 2014, we found 57 cases of supratentorial HBL without VHL as shown in Table 1 . [ 6 8 9 15 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 ] On reviewing the literature, we found that supratentorial HBL affected patients ranging from 3 months to 80 years with maximum cases belonging to 20–30 years and 40–50 years age group. Among the infants, only one case was found, thus making it a rare tumor in infancy.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…[ 9 ] To this date, 56 cases of acute hemorrhage have been described with an underlying HGB. [ 1 2 3 5 6 7 10 11 15 16 17 18 20 22 23 24 25 31 33 34 35 37 41 ] A total of 19 cases have been described in the posterior fossa. Large hemorrhages related to HGBs have been described more commonly in spinal locations.…”
Section: Discussionmentioning
confidence: 99%